Practical guides on credit and business transactions : relevant laws commentaries & jurisprudence - Apolo, Jose T. (Mandaluyong City, Philippines : National Book Store, 2005)
This book will be additional reference material for lawyers and students of law.
Part 1. Laws affecting credit transactions -- Part 2. Ways to secure credit transactions -- Part 3. Other relevant laws affecting credit transactions -- Part 4. Digests of relevant supreme court rulings -- Part 5. Indica of fraud and other palusot schemes; tips on how to prevent fraud.
Keywords: BUSINESS LAW